휴대용 방사선 측정시스템의 최고값 검출 알고리즘의 설계 및 구현 - Oh, JaeKyun (The Graduate School, Ajou University, 2016)
Abstract Although more than 30 years has already passed since the Chernobyl nuclear accident occurred on April 26, 1986, the damage resulting from the radioactive effluent is still in progress. Even now when more than four years has passed since the occurrence of the Fukushima nuclear plant explosion accident on March 11, 2011 due to the aftermath of the great east Japan earthquake, let alone the aggregation of the damage, radiation leaks are continuing. According to a recent announcement of the Bedford Institute of Oceanography under the umbrella of the Department of Marine and Fisheries of Canada, the concentration of Cs-137 has been increasing from 3Bq/㎥(June 2012) to 0.76Bq/㎥(2013) and to 2.03Bq/㎥(2014) in seawater in the coast of Canada, several thousand kilometers away from Fukushima. This is information can be said to be a sufficient reason for the perception that South Korea cannot be guaranteed for safety against radioactivity. Therefore, the necessity of not only studies for easy detection of radioactivity but also the propagation of related information has become a pressing issue directly related to our survival and the fact that radioactivity is not only the problem of Chernobyl or Fukushima only known through reports should be perceived now. In fact, the risk of direct radiation exposure has been caused to our dietary life and if we paid just a little attention, we could find radio-active wastes as by-products of medical practice without difficulty at hospitals close to us. The moving paths of radioactive substances predicted based on oc-ean currents and marine debris convergence are expected to be conti-nuously accumulated and consequences of contamination increase over time. The possibility of radiation exposure of all mankind will increase and the studies and supply of high performance state-of-the-art d-etectors of radiation exposure can be also said to be urgent. As a solution for such problems, this researcher studied methods of improving existing detectors using analog boards and proposes a sof-tware algorithm for prevention of not only the degradation of detection performance due to noises, etc. occurring on the analog board but also the occurrence of unnecessary power consumption due to the operation of the analog board and the phenomenon of degradation of detector performance due to the signals inevitably ignored in the pro-cess of pulse shaping in the analog board signal process.
학위논문(박사)--아주대학교 일반대학원 :의용공학과정,2016. 2
Keywords: Radiation Detector; Peak Detection Algorithm; Digital Radiation Detection